Evaluation the effect of laparoscopic unilateral ovariectomy in young Iraqi black goat on the histomorphometric of the remaining ovary at adult stage: K. I. Al-Khazraji1; M. J. Eesa2 and S. M. Merhesh3 - Eesa, M. J. (The Iraqi Journal of Veterinary Medicine, 2016)
The ovarian histomorphometric in adult normal and unilateral ovariectomized Iraqi black goats (Age 7 months) was studied to evaluate the effect of laparoscopic unilateral ovariectomy of young goat (age 2-3 months) on other remaining ovary histologically. Ten young female Iraqi black goats were used in the study. The goats were divided randomly into two equal groups; young goats were left normal (group A) and young goats underwent to right laparoscopic unilateral ovariectomy (group B). All animals in both groups were left to reach adult stage at 7 months age, in which they underwent to removal their ovaries laparoscopically by using the harmonic scalpel. Operations were performed under general anesthesia by using of a mixture of xylazine and ketamine intramuscularly. The ovarian histomorphometric included; height of germinal epithelium and thickness of tunica albuginea, cortex and medulla were measured at adult stage for both groups. The study revealed a significant elevation (P<0.05) in thickness value of tunica albuginea, cortex and medulla in the right ovary compared with the left one in normal adult goat (group A). The left ovary in group (B) showed significant increase in the thickness value of tunica albuginea, cortex and medulla compared with those in similar (left) ovary in group (A) which indicated that the remaining ovary in group (B) showed compensatory action in increasing their histological structures measurements. The short operative time, no intraoperative and less postoperative complications referred to that the laparoscopic ovariectomy in goats could be performed successfully with this technique and by using of harmonic scalpel.